2006
DOI: 10.1103/physrevb.74.155210
|View full text |Cite
|
Sign up to set email alerts
|

Doping front propagation in light-emitting electrochemical cells

Abstract: Observations of the expansion of the p-and n-doped regions in planar ͑lateral͒ polymer light-emitting electrochemical cells with large ͑mm-sized͒ interelectrode gaps driven with 5 to 50 V have inspired a model describing the doping front propagation. We find that the propagation is limited by the movement of ions in the electronically insulating region between the p-and n-doped regions. Two consequences of an ion-limited front propagation are that the doping fronts accelerate as they approach each other, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 28 publications
5
65
0
Order By: Relevance
“…In a previous paper, 9 we demonstrated that the dopingfront progression observed during turn on in LECs is limited by the transport of ions between the doping fronts, where neutral polymer is oxidized and reduced to p-doped and n-doped polymers, respectively. A sketch of this process occurring in a planar device with Au electrodes covered by a mixture of a conjugated polymer and electrolyte is shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In a previous paper, 9 we demonstrated that the dopingfront progression observed during turn on in LECs is limited by the transport of ions between the doping fronts, where neutral polymer is oxidized and reduced to p-doped and n-doped polymers, respectively. A sketch of this process occurring in a planar device with Au electrodes covered by a mixture of a conjugated polymer and electrolyte is shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…9 requires that the electronic current consumed by the device be proportional to the rate of doping-front propagation during device turn on; in other words that the doping-front progression produces a constant doping concentration behind the front. A comparison between the p-doping-front position and integrated current ͑charge͒ versus time is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total measured current in LECs comprises an ionic and an electronic part, where the former dominates during the initial operation [49] and the latter ideally should be solely existent during steadstate operation [48]. The observed drop in current during the UV-exposure step in Fig.…”
Section: Fig 3 Ftir Spectra Recorded On a {Poly-peo:metma/amps:dmpamentioning
confidence: 88%
“…[31][32][33][34][35][36] However, the further development of LECs is currently hampered by an inadequate understanding of the device operation. In fact, an active debate regarding the fundamental nature of LEC operation has continued for more than a decade, and two distinct models are competing for acceptance: the electrochemical doping model 18,32,[37][38][39][40] and the electrodynamic model 36,[41][42][43][44] . In order to distinguish them, it is appropriate to establish the electrostatic potential profile in a device during steady-state operation, as the models predict distinctly differing profiles.…”
mentioning
confidence: 99%